Politics and Policies of Health Systems: Reflections on 50 Years of Observing Protests, Leaders, and Political Analysis - Michael R. Reich (Taylor & Francis Group, 2023)
ABSTRACTThis commentary presents reflections on my work over the past five decades related to the politics and policies of health systems from various perspectives. The essay is based on a plenary lecture at the Seventh Global Symposium on Health Systems Research in Bogotá, Colombia, in November 2022. The commentary examines a central concern in many of my writings-and a persistent challenge for people working to improve public health: How can the powerless influence policy? Using examples drawn from my past writings, I discuss three broad themes related to this question: the role of social protest movements, the impact of political leadership, and the relevance of political analysis. These reflections are offered in the hope of expanding the use of applied political analysis in public health, and thus contributing to improved health and health equity in the world.